2006
DOI: 10.1212/01.wnl.0000191303.91188.00
|View full text |Cite
|
Sign up to set email alerts
|

Amygdala fMRI lateralizes temporal lobe epilepsy

Abstract: fMRI activation of the amygdala evoked by an animated fearful face paradigm is strong, reproducible, and specific in individual subjects. The combination of the fearful face paradigm and Roland's Hometown Walking Task provides a more reliable presurgical mapping of mesial temporal lobe structures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 37 publications
4
47
1
Order By: Relevance
“…These results diverge from expected results of bilaterality in the domain of non-verbal encoding. The individual lateralization indices from this task performed by healthy subjects have not been previously discussed to any great extent, even though the task is commonly used both for research and clinical purposes (Jokeit et al 2001b;Schacher et al 2006;Beisteiner et al 2008). One possible explanation is that this visuospatial paradigm was previously studied in patients with known or suspected MTL pathology, but has not been systematically studied in healthy subjects at an individual level.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results diverge from expected results of bilaterality in the domain of non-verbal encoding. The individual lateralization indices from this task performed by healthy subjects have not been previously discussed to any great extent, even though the task is commonly used both for research and clinical purposes (Jokeit et al 2001b;Schacher et al 2006;Beisteiner et al 2008). One possible explanation is that this visuospatial paradigm was previously studied in patients with known or suspected MTL pathology, but has not been systematically studied in healthy subjects at an individual level.…”
Section: Discussionmentioning
confidence: 99%
“…Various paradigms aim at visualizing the encoding process and the choice of either an event-related or a block-designed paradigm may affect the activation patterns in the limbic system and the hippocampus (Powell et al 2005). Furthermore, different aspects of the memory process activate different areas within the MTL structures (Àvila et al 2006;Schacher et al 2006). When a pre-defined anatomical region of interest is used to test an a priori hypothesis, the choice of the location and the size of the area in itself are of crucial importance.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the choice of optimal imaging parameters for the amygdala is disputable and contradicting opinions were published. A number of authors recommend a coronal section orientation to obtain the optimal amygdala activations, [3,13] which has resulted in this orientation often being used in fMRI studies aimed at the amygdala (e.g., [14,15]). Robinson et al [16] measured the main magnetic field variation across the amygdalae and found comparable changes in the craniocaudal and anterior-posterior directions, and slightly lower in the left-right direction.…”
Section: Discussionmentioning
confidence: 99%
“…Based on that, one can expect that amygdalo-perirhinal and amygdalo-entorhinal disconnections may strongly affect emotional processing (including emotional memories) in humans. The evidence supporting these speculations comes from the fMRI study of Schacher and coworkers [30] who described the abnormal response of the amygdala and temporal cortex contralateral to the seizure focus in patients with TLE when they were presented with fearful faces (the bilateral activation of the amygdaloid complex was observed in controls). A subpopulation of these patients also had dissociated amygdala and parahippocampal responses compared with controls.…”
Section: Changes In Connectivities Between Structures Involved In Feamentioning
confidence: 95%